2021
DOI: 10.1002/poc.4205
|View full text |Cite
|
Sign up to set email alerts
|

An efficient colorimetric inspection of ammonia using silver nanoparticles synthesized by 3‐(1‐(2‐(2,4‐dinitrophenyl)hydrazono)ethyl)‐1H‐indole as chemo‐sensors in water environment

Abstract: We synthesized 3-(1-(2-(2,4-dinitrophenyl)hydrazono)ethyl)-1H-indole by condensed of 3-acetylindole with 2,4-dinitrophenylhydrazine used as chemo sensor for ammonia. Silver nanoparticles were prepared using a straightforward strategy technique of chemical reduction process by hydrazine derivative (HD) at room temperature. HD has been utilized as a reducing and stabilizer; that is, no other capping agent needed to guide the anisotropic formation of Ag-NPs. UV/Vis spectroscopy was used to evaluate the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…However, these methods have some limitations, such as slow processing times, high operating temperatures, and specialized expensive equipment requirements. 1 Among these methods, spectroscopic strategies are simpler and cheaper, especially when plasmonic nanoparticles are part of the sensor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these methods have some limitations, such as slow processing times, high operating temperatures, and specialized expensive equipment requirements. 1 Among these methods, spectroscopic strategies are simpler and cheaper, especially when plasmonic nanoparticles are part of the sensor.…”
Section: Resultsmentioning
confidence: 99%
“…The detection limit of ammonia in the present study is lower than the reported methods. 1,[31][32][33][34][36][37][38][39] Most reports do not provide visual detection 1,[30][31][32][33][34]36,39 or clear color differentiation. 35,38 In the present study, the color changes of the sensor in the absence and presence of different ammonia concentrations are completely different and can be easily detected by the naked eye.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation